Asthma is not Enough: Continuation of Smoking Among Parents with an Asthmatic Child - Joel J Liem; Anita L Kozyrskyj; Cecilia M Benoit; Allan B Becker (Canadian Respiratory Journal)
BACKGROUND: Ideally, on diagnosis of asthma in a child, parents are counselled to decrease environmental tobacco smoke exposure to their children.